ANALISIS PENGENDALIAN BIAYA PRODUKSI UNTUK MENILAI EFISIENSI DAN EFEKTIVITAS BIAYA PRODUKSI - Massie, Novela Irene Karly; Saerang, David P. E.; Tirayoh, Victorina Z. (Universitas Sam Ratulangi, 2018)
Company management is a series of actions undertaken by members of the organization in an effort to achieve organizational goals. Management has an important role in controlling production costs where the efficiency and effectiveness of production cost control is valued by cost centers ability to achieve expected production volume. The purpose of this research is to know how to control the production cost, to evaluate the efficiency of production cost at Pak Untung tofu factory at Teling Atas, Manado. The method used is qualitative descriptive. The result of this research shows that pak Untung tofu business has not done a good production cost control due to lack of cost planning that does not set the standard cost so that in a few months raw material purchase has increased the purchase price of raw materials.Keywords : Control of production costs, efficiency, and effectiviness